One-Pot, Four-Component Synthesis of Novel Imidazo[2,1-b]thiazol-5-amine Derivatives - Mahdavi, Mohammad; Asadi, Mehdi; Saeedi, Mina; Ebrahimi, Mostafa; Rasouli, Mohammad A.; Ranjbar, Parviz R.; Foroumadi, Alireza; Shafiee, Abbas (Synthesis, 2012)
Novel imidazo[2,1-b]thiazol-5-amine derivatives were synthesized by a one-pot, four-component reaction of 2-bromoacetophenone derivatives, aromatic aldehydes, thiourea, and isocyanides in the presence of ammonium chloride (NH4Cl) in toluene under reflux conditions. Moderate to good yields resulted and the reaction showed tolerance toward a range of aromatic aldehydes with electron-donating and electron-withdrawing substituents on either para or ortho positions.
Keywords: heterocyclic compounds; multicomponent reactions; isocyanides; thiourea; ammonium chloride